DINÁMICA DE LA CUERDA BOSÓNICA CIRCULAR - Villegas Silva, Fulgencio (2009)
After a brief discussion about the Nambu-Goto action, we introduce the concept of transverse velocity and find it for a closed circular bosonic string, then we study and solve the string’s equations of movement by using the energy conservation law and finally we sketch its corresponding world sheet.